FINANCIAL DISTRESS: LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - anastasia, anastasia; Sri Ayem (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Financial distress indicates a condition when the company experiences financial difficulties that cause bankruptcy. This study aims to determine the effect of liquidity, leverage, and profitability on financial distress with company size as moderation. The population in this study were non-primary consumer goods sub-sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sample determination was carried out by purposive sampling so that 21 companies with 84 annual financial reports were obtained. The data analysis technique uses multiple linear regression and moderated regression analysis (MRA) using SPSS 25. The results showed that liquidity, leverage, and profitability have a positive and significant effect on financial distress. Company size moderates by weakening the effect of liquidity and leverage on financial distress. However, company size is unable to moderate the effect of profitability on financial distress. The results of this study are expected to help company management in managing aspects related to liquidity, leverage, and profitability to avoid financial distress